Solve for x
x = \frac{\sqrt{5961} + 107}{175} \approx 1.052614358
x=\frac{107-\sqrt{5961}}{175}\approx 0.170242785
Graph
Share
Copied to clipboard
7x^{2}-8.56x+1.2544=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-8.56\right)±\sqrt{\left(-8.56\right)^{2}-4\times 7\times 1.2544}}{2\times 7}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 7 for a, -8.56 for b, and 1.2544 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-8.56\right)±\sqrt{73.2736-4\times 7\times 1.2544}}{2\times 7}
Square -8.56 by squaring both the numerator and the denominator of the fraction.
x=\frac{-\left(-8.56\right)±\sqrt{73.2736-28\times 1.2544}}{2\times 7}
Multiply -4 times 7.
x=\frac{-\left(-8.56\right)±\sqrt{\frac{45796-21952}{625}}}{2\times 7}
Multiply -28 times 1.2544.
x=\frac{-\left(-8.56\right)±\sqrt{38.1504}}{2\times 7}
Add 73.2736 to -35.1232 by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
x=\frac{-\left(-8.56\right)±\frac{2\sqrt{5961}}{25}}{2\times 7}
Take the square root of 38.1504.
x=\frac{8.56±\frac{2\sqrt{5961}}{25}}{2\times 7}
The opposite of -8.56 is 8.56.
x=\frac{8.56±\frac{2\sqrt{5961}}{25}}{14}
Multiply 2 times 7.
x=\frac{2\sqrt{5961}+214}{14\times 25}
Now solve the equation x=\frac{8.56±\frac{2\sqrt{5961}}{25}}{14} when ± is plus. Add 8.56 to \frac{2\sqrt{5961}}{25}.
x=\frac{\sqrt{5961}+107}{175}
Divide \frac{214+2\sqrt{5961}}{25} by 14.
x=\frac{214-2\sqrt{5961}}{14\times 25}
Now solve the equation x=\frac{8.56±\frac{2\sqrt{5961}}{25}}{14} when ± is minus. Subtract \frac{2\sqrt{5961}}{25} from 8.56.
x=\frac{107-\sqrt{5961}}{175}
Divide \frac{214-2\sqrt{5961}}{25} by 14.
x=\frac{\sqrt{5961}+107}{175} x=\frac{107-\sqrt{5961}}{175}
The equation is now solved.
7x^{2}-8.56x+1.2544=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
7x^{2}-8.56x+1.2544-1.2544=-1.2544
Subtract 1.2544 from both sides of the equation.
7x^{2}-8.56x=-1.2544
Subtracting 1.2544 from itself leaves 0.
\frac{7x^{2}-8.56x}{7}=-\frac{1.2544}{7}
Divide both sides by 7.
x^{2}+\left(-\frac{8.56}{7}\right)x=-\frac{1.2544}{7}
Dividing by 7 undoes the multiplication by 7.
x^{2}-\frac{214}{175}x=-\frac{1.2544}{7}
Divide -8.56 by 7.
x^{2}-\frac{214}{175}x=-0.1792
Divide -1.2544 by 7.
x^{2}-\frac{214}{175}x+\left(-\frac{107}{175}\right)^{2}=-0.1792+\left(-\frac{107}{175}\right)^{2}
Divide -\frac{214}{175}, the coefficient of the x term, by 2 to get -\frac{107}{175}. Then add the square of -\frac{107}{175} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{214}{175}x+\frac{11449}{30625}=-0.1792+\frac{11449}{30625}
Square -\frac{107}{175} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{214}{175}x+\frac{11449}{30625}=\frac{5961}{30625}
Add -0.1792 to \frac{11449}{30625} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x-\frac{107}{175}\right)^{2}=\frac{5961}{30625}
Factor x^{2}-\frac{214}{175}x+\frac{11449}{30625}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{107}{175}\right)^{2}}=\sqrt{\frac{5961}{30625}}
Take the square root of both sides of the equation.
x-\frac{107}{175}=\frac{\sqrt{5961}}{175} x-\frac{107}{175}=-\frac{\sqrt{5961}}{175}
Simplify.
x=\frac{\sqrt{5961}+107}{175} x=\frac{107-\sqrt{5961}}{175}
Add \frac{107}{175} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}